Revolution in Learning Moral Beliefs: Development of Interactive Video Media to Improve Student Motivation and Learning Outcomes - Mia Aisyah Rahma; Triyo Supriyatno; Abd. Gafur (Al-Qalam Institute, 2024)
This study investigates the impact of interactive video-based learning media on student motivation and learning outcomes in primary education. Despite the growing use of digital media in education, many students still struggle with abstract material and low motivation. The research aims to test whether interactive video can enhance these areas. A quasi-experimental design was used with 26 fourth-grade students from MI Almaarif 02 Singosari, Malang, employing purposive sampling. Data were collected through pretest and posttest assessments and surveys on student motivation. Statistical analysis included paired t-tests and regression analysis to examine the relationship between interactive video media use and improvements in motivation and academic performance. The results indicate a significant positive effect, with the experimental group showing a higher N-Gain (0.82) compared to the control group (0.57), supporting the hypothesis that interactive media improves both motivation and learning outcomes (p < 0.001). These findings contribute to the literature by demonstrating the efficacy of interactive video in religious education, providing valuable insights for educators and policymakers. The study suggests further research to explore long-term impacts and the potential for broader application across diverse educational contexts.